2017
DOI: 10.1038/s41598-017-00886-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface-dependent scenarios for dissolution-driven motion of growing droplets

Abstract: Nano-droplets on a foreign substrate have received increasing attention because of their technological possible applications, for instance to catalyse the growth of nanowires. In some cases the droplets can move as a result of a reaction with the substrate. In this work we show that the substrate orientation, the surface morphology and the shape of the pits etched in the substrate by the droplets affect the droplet motion, so that a single mechanism (droplet-induced substrate dissolution) may lead to several u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Droplet 1 is at the local hot spot and is, thus, fully in equilibrium, whereas the other droplets are on their way to the hot spot. Such motion in the direction of the highest temperature has also been observed for the similar eutectic systems [4][5][6][7][8][9][10]. In the following sections we discuss important characteristics of the morphology of the eutectic PtGe droplets as revealed by PEEM.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Droplet 1 is at the local hot spot and is, thus, fully in equilibrium, whereas the other droplets are on their way to the hot spot. Such motion in the direction of the highest temperature has also been observed for the similar eutectic systems [4][5][6][7][8][9][10]. In the following sections we discuss important characteristics of the morphology of the eutectic PtGe droplets as revealed by PEEM.…”
Section: Resultssupporting
confidence: 59%
“…Applications involve the growth of the two-dimensional material germanene [2] or standing-up Si nanowires [3] from the eutectic dropletx. Several of these eutectic systems have been studied by surface electron microscopy [4][5][6][7][8][9][10]. Information on the three-dimensional (3D) details of these liquid droplets, however, is rarely obtained from electron microscopy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Such hierarchy in the surface etching by Au atoms and facets formation is also observed for singlecomponent semiconductors such as Si or Ge 48,49 .…”
Section: /31mentioning
confidence: 58%
“…Horizontal nanowires can also be grown on Si(110). We have shown that during Au deposition on Si(110) at temperatures higher than the eutectic temperature (633 K) elongated liquid droplets form, move on the substrate along a unique axis but in both directions ( [1][2][3][4][5][6][7][8][9][10] and [-110]) and leave in-plane Si nanowires at their back [12,13]. The randomness of the motion direction of the droplet limits the degrees of control and thus the perspectives of possible applications.…”
Section: Introductionmentioning
confidence: 99%